1997
DOI: 10.1002/cjce.5450750507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of catalyst loading on gasliquid mass transfer in a slurry reactor: A statistical experimental approach

Abstract: A statistical experimental design was employed to study the effects of pressure, temperature, catalyst loading, and mixing speed on the solubilities (P) and volumetric gadliquid mass transfer coefficients (kLa) for H,, N,, CO, CH, and C,H, in a liquid mixture of hexanes containing iron oxide catalyst in a 4-litre agitated autoclave. Statistical correlations for k,a values for the gases used were developed. Mixing speed and solid concentration showed the strongest effects on k,a. At low catalyst concentrations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…It is worth noting that in the stirred tank reactors, the volumetric gas–liquid or liquid–solid mass transfer coefficient has been reported first to increase with an increase of the solid or catalyst loading and then to decrease after reaching a maximum. 55 , 56 Thus, there might exist an optimal solid catalyst amount to ensure the desired mass transfer rate and reaction performance.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is worth noting that in the stirred tank reactors, the volumetric gas–liquid or liquid–solid mass transfer coefficient has been reported first to increase with an increase of the solid or catalyst loading and then to decrease after reaching a maximum. 55 , 56 Thus, there might exist an optimal solid catalyst amount to ensure the desired mass transfer rate and reaction performance.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Satterfield and Huff [262] concluded that the hydrogen mass transfer was the limiting step for reactor productivity, whereas Deckwer [104] showed that the mass transfer resistance was small compared to the kinetics resistance. Inga and Morsi [418] and Sehabiague and Morsi [111,259] reported that F-T SBCRs operating under a kinetically-controlled regime at low catalyst concentrations could move to a mass transfer-controlled regime at high catalyst concentrations, where the reactor performance quickly declines. Nonetheless, it is generally agreed that the mass transfer strongly depends on the bubble size, where smaller bubbles result in a greater gas-liquid interfacial area, which improves the mass transfer.…”
Section: Mass Transfermentioning
confidence: 98%
“…The effects of mass transfer on three-phase reactor performance have been extensively investigated in the literature [109,111,[258][259][260][261]. Earlier studies on the mass transfer focused on the significance of hydrogen mass transfer compared to the overall reaction resistance.…”
Section: Mass Transfermentioning
confidence: 99%
“…(24) to calculate k L a for small and large gas bubbles using their corresponding gas holdup and Sauter mean bubble diameter is a more accurate approach than the ones used by de Swart and Krishna (2002) and Grund et al (1992); because it underscores the fact that the mass transfer behavior of SBCRs is controlled by the gas-liquid interfacial area (Behkish et al, 2002;Inga and Morsi, 1997;Lemoine et al, 2004). All the correlations listed in Table 1 were used in the simulator according to the algorithm developed by with the exception of the mass transfer coefficients of small gas bubbles which was obtained from:…”
Section: Hydrodynamics and Mass Transfer Correlationsmentioning
confidence: 99%